Predicting Cardiovascular Stent Complications Using Self‐Reporting Biosensors for Noninvasive Detection of Disease (Adv. Sci. 15/2022). Issue 15 (25th May 2022) - Hoare, Daniel; Tsiamis, Andreas; Marland, Jamie R. K.; Czyzewski, Jakub; Kirimi, Mahmut T.; Holsgrove, Michael; Russell, Ewan; Neale, Steven L.; Mirzai, Nosrat; Mitra, Srinjoy; Mercer, John R.
Abstract : Self‐Reporting Biosensors In article number 2105285, John R. Mercer and co‐workers develop an implantable miniaturised sensor and telemetry system that can detect and discern different cell types associated with in stent restenosis, distinguish sub‐plaque components and differentiate blood from blood clot. This work shows that microfabricated sensors can be used for both stent and grafts implantables to provide clinically actionable data.